Incidence of potential drug interactions in medication prescriptions for children and adolescents in the University Hospital Olomouc, Czech Republic - Langerová, Petra; Prokeš, Michal; Konvalinka, Martin; Fürstová, Jana; Urbánek, Karel (European journal of pediatrics, 2013)
UNLABELLED: Drug interactions are important potential causes of adverse drug reactions. However, studies of their occurrence in children are almost entirely lacking. This study evaluates the incidence of potential drug interactions (PDIs) in medication prescriptions for children. The study was performed at the University Hospital in Olomouc. PDIs in each patient's prescriptions were identified. Multivariate analysis was performed in order to assess the risk factors confounding the potential interactions. Univariate analysis was used to assess which diagnostic groups and medication groups significantly increase or lower the odds of a potential drug-drug interaction. A total of 6,078 patients meeting the inclusion criteria entered the study. They received 19,522 prescriptions. PDIs were identified in 3.83 % of patients (moderate-to-severe cases in 0.47 %). Patient age (p = 0.008), the average number of prescriptions per visit (p < 0.0001), and the number of visits per year (p < 0.0001) were found to increase the risk of drug interaction. The presence of epilepsy, leukemia, or rheumatoid arthritis and related disease diagnoses were discovered to increase the risk of PDIs significantly. CONCLUSION: The risk of PDIs in children is low, but it increases significantly with age and the number of drugs prescribed, particularly antiepileptics and immunosuppressants. The finding of a potential interaction in 0.47 % of all children in whom any medication was prescribed should not be underestimated since it means a significant risk for one child out of every 200, and it is also substantially higher in the chronically ill. Pediatricians should be aware of relevant interactions and should prevent them by therapeutic drug monitoring or appropriate clinical and laboratory monitoring.
Keywords: Drug Monitoring; Infant; Humans; kojenec; dítě; lékové interakce; monitorování léčiv; Child; nemocnice univerzitní; Female; rizikové faktory; mladý dospělý; Hospitals, University; lékové předpisy; lidé; Drug Interactions; předškolní dítě; ženské pohlaví; Male; Retrospective Studies; Adolescent; incidence; Incidence; Czech Republic; Young Adult; retrospektivní studie; Risk Assessment; Česká republika; mužské pohlaví; Child, Preschool; Drug Prescriptions; hodnocení rizik; mladiství; Risk Factors